Reducing insulin via conditional partial gene ablation in adults reverses diet‐induced weight gain. Issue 3 (3rd January 2018) - Page, Melissa M.; Skovs, Søs; Cen, Haoning; Chiu, Amy P.; Dionne, Derek A.; Hutchinson, Daria F.; Lim, Gareth E.; Szabat, Marta; Flibotte, Stephane; Sinha, Sunita; Nislow, Corey; Rodrigues, Brian; et al.
Abstract : Excess circulating insulin is associated with obesity in humans and in animal models. However, the physiologic causality of hyperinsulinemia in adult obesity has rightfully been questioned because of the absence of clear evidence that weight loss can be induced by acutely reversing diet‐induced hyperinsulinemia. Herein, we describe the consequences of inducible, partial insulin gene deletion in a mouse model in which animals have already been made obese by consuming a high‐fat diet. A modest reduction in insulin production/secretion was sufficient to cause significant weight loss within 5 wk, with a specific effect on visceral adipose tissue. This result was associated with a reduction in the protein abundance of the lipodystrophy gene polymerase I and transcript release factor ( Ptrf; Cavin) in gonadal adipose tissue. RNAseq analysis showed that reduced insulin and weight loss also associated with a signature of reduced innate immunity. This study demonstrates that changes in circulating insulin that are too fine to adversely affect glucose homeostasis nonetheless exert control over adiposity.—Page, M. M., Skovsø, S., Cen, H., Chiu, A.P., Dionne, D.A., Hutchinson, D.F., Lim, G.E., Szabat, M., Flibotte, S., Sinha, S., Nislow, C., Rodrigues, B., Johnson, J. D. Reducing insulin via conditional partial gene ablation in adults reverses diet‐induced weight gain. FASEB J. 32, 1196–1206 (2018). www.fasebj.org